The psychology of language from data to theory - Harley, Trevor A. (Psychology Press, 2014)
"Now in full colour, this fully revised edition of the best-selling textbook provides an up-to-date and comprehensive introduction to the psychology of language for undergraduates, postgraduates, and researchers. It contains everything the student needs to know about how we acquire, understand, produce, and store language. Whilst maintaining both the structure of the previous editions and the emphasis on cognitive processing, this fourth edition has been thoroughly updated to include: the latest research, including recent results from the fast-moving field of brain imaging and studies updated coverage of key ideas and models an expanded glossary more real-life examples and illustrations. The Psychology of Language, Fourth Edition is praised for describing complex ideas in a clear and approachable style, and assumes no prior knowledge other than a grounding in the basic concepts of cognitive psychology. It will be essential reading for advanced undergraduate and graduate students of cognition, psycholinguistics or the psychology of language. It will also be useful for those on speech and language therapy courses. The book is supported by a companion website featuring a range of helpful supplementary resources for both students and lecturers"--